Adherence to fat diets by students of a bodybuilding gym in Bauru city - Almeida, Thais Ferraz de; Souza, Carolina Tarcinalli; Souza, Debora Tarcinalli; Togneri Ferron, Artur Junio [UNESP]; Francisqueti-Ferron, Fabiane Valentini (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
Introduction: The adoption of fad diets has become very common, with great acceptance by the public. Aim: The aim of the study was to verify the adherence of fad diets by users of a Bauru gym. Materials and methods: A cross-sectional study was carried out with 130 people attending a gym in the city of Bauru SP. Data were collected through a questionnaire with 21 questions. Results: The majority of the sample consisted of women (51.5%), and the mean age was 33.9 years +/- 12.6 years. Regarding the type of exercise practiced by the study population, 57.7% practiced only bodybuilding, 2.34% in collective classes and both exercises 39.23%. 58.46% had already had some kind of diet, with the most frequent being low carb diet (21.54%), intermittent fasting (16.92%) and weight loss shakes (10.77%). 50.77% reported that they already had nutritional guidance, of which 41.54% was with the nutritionist, 13.85% was through physical education teacher and the same 13.85% with endocrine. Conclusion: Thus, it is possible to conclude that many people have already practiced some kind of fad diet and most often without proper guidance, putting their own health at risk.
Keywords: Diet fads; Food idioms; Food trends